ANALISIS PENJATUHAN TINDAKAN TERHADAP ANAK YANG MENGAKSES SISTEM ELEKTRONIK TANPA HAK (STUDI KASUS PUTUSAN NOMOR 52/Pid.Sus-Anak/2019/PN Mks): ANALYSIS OF FOLLOWING ACTION AGAINST CHILDREN ACCESSING THE ELECTRONIC SYSTEM WITHOUT RIGHTS (CASE STUDY DECISION NUMBER 52 / Pid.Sus-Anak / 2019 / PN Mks) - Amanda, Fayelixie Keshia; Zubaidah, Siti (Faculty Of Law Bosowa University, 2021)
This research aims to analyze and comprehend the basic consideration o the judge’s council in penalizing child placement action in Social Welfare Management Agency on Verdict Number 52/Pid.Sus-Anak/2019/PN Mks.Also to acknowledge the elements of children accesing electronic systems without rihgts.Conseuently,research is needed using certain data record’s method,which consist of literature study,documents study,and in depth interview considering referred laws. The research’s result shows that in penalizing child placement action of accesing electronics system without rights,the judge’s council considered education,health,and children’s social rights.the judge’s council considered education,health,and children’s social rights to penalizing action from the lowest to the highest.Judges’consideration arbitres to the reerred crime case taken,the pattern of the crime case,enviromental and family factors.The deportation of the placement in Social Welfare Management Agency is still regarding to justice and humanity. Besides,the elements of crime case of children accesing electronic system without rights,whose in this verdict accused Jepri bin Junaidi;purposely against law elements;accesing computer/electronic system of facebook group LEMBAGA INFO KEJADIAN MAKASSAR KOTA(L-IKMK)Lacapila.com elements;hacking securty system with chronological actions begin with accesing similar Yahoo email account,accesing victim’s facebook group,and sold the group page,as what eplicitely mentioned in Laws of Electronic Information and Transaction.